2020
DOI: 10.1590/0001-3765202020181052
|View full text |Cite
|
Sign up to set email alerts
|

Palynological analysis of the genus Dryopteris Adans. (Dryopteridaceae) in Argentina

Abstract: The spore morphology and wall ultrastructure of Dryopteris fi lix-mas, D. patula and D. wallichiana from Argentina were studied using light microscope, scanning and transmission electron microscope. The study was carried out with herbarium material from Argentine institutions. Equatorial diameters, polar diameters and laesura length were measured. The spores are monoletes with a rugate ornamentation. The folds are short to long, infl ate, irregular in shape and size, and varying from subglobose to elongate.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Spore morphology of fern species has been observed and described under light microscopy (LM) and scanning electron microscopy (SEM) in previous studies (e.g., Nayar & Devi 1964;Gastony 1974;Morbelli 1976;Tryon & Lugardon 1991;Giudice et al 2004;Moran et al 2007;Ramos Giacosa et al 2015, 2016Gorrer et al 2020Gorrer et al , 2022. In these studies, differences in shape, size, aperture characters and wall ornamentation were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Spore morphology of fern species has been observed and described under light microscopy (LM) and scanning electron microscopy (SEM) in previous studies (e.g., Nayar & Devi 1964;Gastony 1974;Morbelli 1976;Tryon & Lugardon 1991;Giudice et al 2004;Moran et al 2007;Ramos Giacosa et al 2015, 2016Gorrer et al 2020Gorrer et al , 2022. In these studies, differences in shape, size, aperture characters and wall ornamentation were reported.…”
Section: Introductionmentioning
confidence: 99%